Fire Safety Socialization for Elementary School Students Through Evacuation Route and Assembly Point Introduction at SDIT Nurul Ilmi Balikpapan - Nadifa Neeha Wibowo; Indah Rahayu; Devi Ramadan Yanti; Intan Nur Rahman; Danu Adi Prastiyo; Lalita Suci Ramadhani; Retnowaty Retnowaty; Besse Intan Permata Sari; Prita Indriawati (EUNOIA, 2026)
Fire is one of the most serious threats to safety in schools. Lack of knowledge about evacuation procedures and safety symbols can increase the risk of casualties and material losses. This community service activity aimed to provide fire safety education by presenting material on fire evacuation simulations to students at SDIT Nurul Ilmi Balikpapan. The material presented included an understanding of fire simulations, steps to take in the event of a fire, and an introduction to evacuation route symbols and assembly points. The activity was attended by 42 students. The results showed an increase in students' understanding of basic fire safety concepts, awareness of the importance of evacuation routes, and the ability to recognize safety symbols. This education is expected to foster a culture of emergency response in elementary schools and strengthen the implementation of K3 principles.